Experimental characterization of a quantum many-body system via higher-order correlations - Schweigler, Thomas; Kasper, Valentin; Erne, Sebastian; Gasenzer, Thomas; Berges, Jürgen (Nature, 2017)
Quantum systems can be characterized by their correlations1,2. Higher-order (larger than second order) correlations, and the ways in which they can be decomposed into correlations of lower order, provide important information about the system, its structure, its interactions and its complexity3,4. The measurement of such correlation functions is therefore an essential tool for reading, verifying and characterizing quantum simulations5. Although higher-order correlation functions are frequently used in theoretical calculations, so far mainly correlations up to second order have been studied experimentally. Here we study a pair of tunnel-coupled one-dimensional atomic superfluids and characterize the corresponding quantum many-body problem by measuring correlation functions. We extract phase correlation functions up to tenth order from interference patterns and analyse whether, and under what conditions, these functions factorize into correlations of lower order. This analysis characterizes the essential features of our system, the relevant quasiparticles, their interactions and topologically distinct vacua. From our data we conclude that in thermal equilibrium our system can be seen as a quantum simulator of the sine-Gordon model6,7,8,9,10, relevant for diverse disciplines ranging from particle physics to condensed matter11,12. The measurement and evaluation of higher-order correlation functions can easily be generalized to other systems and to study correlations of any other observable such as density, spin and magnetization. It therefore represents a general method for analysing quantum many-body systems from experimental data.